POTENTIALS OF SIMPING TEMPLE SITES AS HISTORY TOURISM BASED ON LOCAL CEREMONY VALUES: (Case Study in Sumberjati Village, Kademangan District, Blitar Regency) - Fandu Dyangga Pradeta; Denny Arinanda Kurnia (JOSAR (Journal of Students Academic Research), 2019)
The Blitar region has tourism potential that can attract visitors both from its natural attractions and historical attractions. Some tourism objects that are worthy of consideration in this area are spread evenly throughout the Blitar district. In this Kademangan area there are several interesting tourist attractions to visit such as Bukit Bunda, Bukit Bonsai, Kampung Coklat and others. In addition there are also interesting historical tours in this area, one of which is the Simping Temple Historical Site in Sumberjati Kademangan village, Blitar Regency. The purpose of this study was to determine and understand the history of the establishment of the Simping Temple, to find out the socio-cultural conditions of the community around the Simping Temple Historical Site and to understand the potential of the historical tourism object of the Simping Temple in the Kademangan area. The object of this study was in the village area Sumberjati, Kademangan District, Blitar Regency. The subject of this research is the source of the data requested for information in accordance with the research problem formulation. This research uses a descriptive method through a qualitative approach that directly looks at the conditions and phenomena around Simping Temple. Data collection methods used used observation, interviews and documentation studies. This study explains that Simping Temple has potential tourism objects to be developed with the values ​​of local wisdom.